Finite Element Analysis of Cogging Torque and Torque Ripple of Brushless DC Motor - Estabraq Abd-Al Kareem; Amer M.Ali (Wasit Journal of Engineering Sciences)
Brushless DC (BLDC) motors are used in various applications, including industrial, automotive, aerospace, and computers, due to their many benefits. Still, it has some drawbacks, like its cogging torque and torque ripple. A three-phase, 1500-watt, four-pole, inner rotor brushless DC motor was modeled and examined using finite element analysis (FEA) based on Maxwell-2D software to analyze cogging torque at no excitation state and torque ripple at full load condition. Design parameters, including magnet thickness, embrace factor, magnet offset, and initial rotor position, were employed to mitigate their effects on cogging torque and torque ripple. The detailed obtained results will guide BLDC motor designers to select proper values of magnet thickness, embrace factor, offset, and initial rotor position without needing to test many costly produced prototype motors.